The Denotative and Connotative Meanings on the Advertisement of iPhone 13 Relax, It’s Iphone - Verenia Vivian Yip; Setefanus Suprajitno (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
A creative and innovative advertisement is required by a company to attract customers. So, advertisers must utilize an attractive technique to convince the viewers to buy their products and they need to deliver the messages to the customers. To deliver the messages, advertisers employ semiotic modes such as visual mode, linguistic mode, and gestural mode. We analyze the denotative and connotative meanings as expressed through the semiotic resources used and the messages delivered in the iPhone 13 Relax, it’s iPhone video advertisement. We use the theory of the process of signification by Chandler (2017) and semiotic mode as supporting theory. The denotative and connotative meanings of the advertisement is that the iPhone 13 has three features namely water-resistance, long battery life, and durability. The messages that these advertisements create is a brand myth, that is, people do not have to worry when they use iPhone 13 in an unfavorable situation.